Meaning Construction in Ancak Tradition: A Study of Living Qur’an - Ansori, Ibnu Hajar; Wilwadikta, Qur’ani Parang; Prafita, Evi Dwi Intan Mey; Gunawan, Adenoval (QOF, 2023)
The research reveals that the Ancak tradition in Wedoroklurak Village, Candi Sidoarjo, consists of a series of activities aimed at purifying the village in preparation for the upcoming month of Ramadan. Rooted in an understanding of Quranic values, particularly those concerning charity (sedekah) and gratitude (syukur) as outlined in QS. Ibrahim [14]: 7, QS. Luqman [21]: 12, QS. al-Baqarah [2]: 264 and 267, the tradition also embodies the living Quran. Analyzing it through Peter L. Berger's Social Construction perspective, the dialectical interplay of verses within the tradition unfolds in three phases. Firstly, Externalization involves the dialogue between religious figures' ideas about comprehending verses on gratitude and charity with societal elements. Gratitude is construed as an expression of appreciation for Allah's blessings and the village's founding predecessors, expressed through charitable acts and communal prayers. Secondly, Objectivation sees the acceptance of these ideas by the community, institutionalizing them into a collective activity. Community members converge at Mbah Nursinah's tomb, the village's founder, bringing offerings like rice, dishes, fruits, and agricultural products, contributing to communal prayers for the village's founders. Thirdly, Internalization transforms the activity into an integral aspect of community life. Transmitted across generations, this internalization process signifies a robust social construction, where the norms and values of the Ancak tradition become inseparable from the identity and daily life of Wedoroklurak Village's residents.